Enhancing portfolio optimization with machine learning methods - Raimundo, Bernardo (2024)
Raimundo, B., & Bravo, J. M. (2024). Enhancing portfolio optimization with machine learning methods: A comparative study using commodity markets data. In MCIS 2024 Proceedings Article 39 AISEL. https://aisel.aisnet.org/mcis2024/39/ --- This work was supported by national funds through FCT (Fundação para a Ciência e a Tecnologia), under the project UIDB/04152/2020 (DOI: 10.54499/UIDB/04152/2020) - Centro de Investigação em Gestão de Informação (MagIC)/NOVA IMS.